Feasibility of Rent and Tax Incentives for Renovation in Older Residential Neighborhoods - Curry, Clarence F.; Gensch, Dennis H. (Management Science, 1975)
Can city governments take meaningful actions to relieve the growing shortage of rental housing units for low income families without heavy reliance on state or federal support? To answer this question a net present value model is developed from the viewpoint of the existing landlords. Using this model the municipal policies which optimize the objective function of providing the maximum renovated housing units subject to budgetary constraints are identified by a convex programming algorithm. The empirical application of this approach to a Pittsburgh neighborhood indicates that it is possible to increase the quality and quantity of the rental housing stock while actually increasing the municipal net revenue.